Modeling of additive manufacturing processes for metals: Challenges and opportunities. Issue 4 (August 2017) - Francois, M.M.; Sun, A.; King, W.E.; Henson, N.J.; Tourret, D.; Bronkhorst, C.A.; Carlson, N.N.; Newman, C.K.; Haut, T.; Bakosi, J.; Gibbs, J.W.; Livescu, V.; et al.
Highlights: This article focuses on reviewing modeling and simulation effort in metal additive manufacturing taking places at U.S. Department of Energy national laboratories. An integrated computational approach from process-structure-properties-performance is necessary to ultimately enable engineering and optimization to specific performance requirements. Models and simulation tools from processing to performance are being developed at multiple lengths scales to account for the complex structure of additive manufactured metals and to understand their performance response.